Impact of Local Tax Revenue and Regional Levies on Local Own Source Revenue in Banten Province (2019–2023) - Rasyid, Arafatur; Dewi, Siti Ratna Sari (Golden Ratio of Data in Summary, 2026)
This study investigates the influence of local tax revenue and regional levies on local own-source revenue (PAD) in Banten Province during the 2019–2023 period. The objective is to determine whether these fiscal components, individually and collectively, strengthen the capacity of local governments to achieve greater financial independence. A quantitative research approach was applied using secondary data obtained from the official regional budget realization reports. Multiple linear regression analysis, supported by classical assumption tests, was conducted to examine the partial and simultaneous effects of the variables. The results reveal that local tax revenue has a positive and significant effect on local own-source revenue (p < 0.001), while regional levies have a positive but insignificant effect (p = 0.972). Simultaneously, both variables exert a significant joint influence on regional fiscal performance, explaining 63.5% of the variation in PAD (R² = 0.635). These findings support the principles of Fiscal Federalism Theory, which emphasize the role of fiscal decentralization in enhancing local revenue capacity. Practically, the results suggest that optimizing tax collection efficiency and reforming regional levy structures are essential strategies for improving fiscal independence and promoting sustainable regional development in Banten Province.